2016
DOI: 10.1111/tmi.12793
|View full text |Cite
|
Sign up to set email alerts
|

Household experience and costs of seeking measles vaccination in rural Guinea‐Bissau

Abstract: Abstractobjectives Children younger than 12 months of age are eligible for childhood vaccines through the public health system in Guinea-Bissau. To limit open vial wastage, a restrictive vial opening policy has been implemented; 10-dose measles vaccine vials are only opened if six or more children aged 9-11 months are present at the vaccination post. Consequently, mothers who bring their child for measles vaccination can be told to return another day. We aimed to describe the household experience and estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
(16 reference statements)
0
11
0
1
Order By: Relevance
“…MOV may be preventing countries from reaching their immunization targets. By ensuring that children who are already receiving health services are screened and vaccinated during regular health service encounters, addressing the underlying causes of MOV can significantly increase coverage and timeliness with minimal and sustainable cost [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…MOV may be preventing countries from reaching their immunization targets. By ensuring that children who are already receiving health services are screened and vaccinated during regular health service encounters, addressing the underlying causes of MOV can significantly increase coverage and timeliness with minimal and sustainable cost [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines are often given later than scheduled partly because of the ‘restrictive vial-opening policy’. In Guinea-Bissau, focus on not wasting vaccines has led to a policy of not opening Bacillus Calmette–Guérin (BCG) and measles vaccine (MV) vials unless several children are present to be vaccinated [19,20], and similar policies are implemented in Burkina Faso. This policy creates missed vaccination opportunities for many children and leads to delayed vaccination with BCG and MV.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that health workers were worried about accountability for their allotted vaccines based on population estimates for children in their catchment geographic areas. The practice of not opening vials unless a certain minimum number of children were present has been observed in other resource-limited settings [26][27][28][29]. In an analysis of 46 countries, including Burkina Faso, one study revealed that missed opportunities to vaccinate children with MCV were more frequent than for diphtheria-pertussis-tetanus (DPT) vaccine or oral polio vaccine; this may in part be due to the fact that MCV is a lyophilized vaccine and must be discarded within a 6-to 8-h window once reconstituted or at the end of the immunization session, whichever comes first, whereas DPT and polio vaccines can be used as long as the Vaccine Vial Monitor is valid or the vaccine is not expired [30].…”
Section: Discussionmentioning
confidence: 99%